2018
DOI: 10.1136/bmj.k3165
|View full text |Cite
|
Sign up to set email alerts
|

Reducing anaemia in low income countries: control of infection is essential

Abstract: In settings with high infection burdens, iron interventions for anaemia may be neither safe nor effective. Strategies to tackle the global burden of anaemia must take this into account, argue Sant-Rayn Pasricha and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 46 publications
1
73
0
Order By: Relevance
“…The influence of improved WASH on anemia reduction could operate through several possible mechanisms: preventing infections, reducing elevated hepcidin levels, and/or reduced enteropathy causing improved intestinal surface area leading to better iron absorption and reduced loss of nutrients through lower diarrhea prevalence . In relation to infection, a recent Cochrane review looking at the interaction between iron and infections concluded that for anemia control, it is necessary to not only focus on iron deficiency but to tackle infections, particularly in settings subject to high‐infection burden . Our study also shows that in nearly 60% of countries, children who received deworming medication had lower odds of being anemic.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The influence of improved WASH on anemia reduction could operate through several possible mechanisms: preventing infections, reducing elevated hepcidin levels, and/or reduced enteropathy causing improved intestinal surface area leading to better iron absorption and reduced loss of nutrients through lower diarrhea prevalence . In relation to infection, a recent Cochrane review looking at the interaction between iron and infections concluded that for anemia control, it is necessary to not only focus on iron deficiency but to tackle infections, particularly in settings subject to high‐infection burden . Our study also shows that in nearly 60% of countries, children who received deworming medication had lower odds of being anemic.…”
Section: Discussionmentioning
confidence: 73%
“…Among women, education, residence, and maternity status seem to be the most prominent factors to be considered in anemia reduction program planning . We suggest increased efforts to reach the most vulnerable groups, to ensure equitable gains in anemia reduction among all subpopulation groups …”
Section: Discussionmentioning
confidence: 93%
“…The exact role of iron deficiency, as one of the few preventable and treatable causes of anaemia, remains unclear due to its diagnostic challenges in HIV-infected patients in low resource settings [3,4,7]. However iron supplementation has been shown to be a risk factor for infections in areas of high infectious burden [8,9]. Peripheral blood markers for iron deficiency, including erythrocyte indices, serum iron, ferritin, and soluble transferrin receptor (sTfR), have been evaluated but their accuracy is often negatively affected by inflammatory states, and renal and liver conditions, which are common in both the African and HIVinfected populations [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…181 A similar consideration must be made regarding the use of dietary iron supplementation to treat anaemia in low-to moderate-income countries, where aggravating already high rates of infant diarrhoea is a clear risk; reducing inflammation and improving sanitary conditions will be instrumental if oral iron supplementation to treat anaemia is to prove fruitful. 156,182 Impaired gut health is a common reason for poor compliance with dietary iron supplementation regimens, even in high-income countries. 183 There is interest in developing dietary iron supplements that are bioavailable to the host but not the microbiota, hopefully avoiding dysbiosis.…”
Section: Targeting the Pathogenmentioning
confidence: 99%